"This is China's Sputnik Moment": The Politics and Poetics of Artificial Intelligence. Issue 3 (3rd April 2023) - Meng, Bingchun
Abstract : This essay unpacks the politics and poetics of artificial intelligence in contemporary China by drawing on textual data from policy documents and news reports, as well as from ethnographic data collected through fieldwork in Shenzhen and Guiyang. Drawing on this empirical study, I argue that on the one hand, there is convergence between the logic of transnational capital and that of the developmentalist state at the discursive level, while on the other hand, the politics of AI unfolds unevenly at the conjuncture of state policy, political economy of digital technologies, and the actions of key stakeholders.